1991
DOI: 10.2307/2937049
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Diversity Along a Riverside Toposequence in Arctic Alaska

Abstract: Nitrogen and phosphorus pool sizes, distribution, and cycling rates were described and compared for six different ecosystem types occurring along a single toposequence in northern Alaska. The toposequence was located on a series of old floodplains of the Sagavanirktok River, in the northern foothills of the Brooks Range. From tussock tundra in the uplands, the toposequence passed through a relatively dry hilltop heath zone, a hillslope shrub/lupine/Cassiope zone, a footslope Equisetum zone, a wet sedge tundra,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
270
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(305 citation statements)
references
References 50 publications
30
270
5
Order By: Relevance
“…This interpretation is consistent with the results of Jefferies (2002, 2003) who showed that exchangeable NH4 and NO3 ions fell to very low levels at the beginning of the growing season and that P. phryganodes utilized organic N rather than inorganic N, as shown in earlier studies of other Arctic and alpine species (Kielland 1994;Raab et al 1996;Schimel and Chapin 1996;Lipson and Monson 1998). Wilson and Jefferies (1996) also showed that in this salt marsh, net N mineralization rates were either very low or negative in early and mid-summer, a finding similar to the studies of Hart and Gunther (1989), Giblin et al (1991), Jonasson et al (1993Jonasson et al ( , 1996 and Schmidt et al (2007). Although these estimates are based on the use of the buried bag technique which may underestimate net N mineralization rates, as senescing roots and root hairs, which provide a source of N, are not included (Jonasson et al 2004).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This interpretation is consistent with the results of Jefferies (2002, 2003) who showed that exchangeable NH4 and NO3 ions fell to very low levels at the beginning of the growing season and that P. phryganodes utilized organic N rather than inorganic N, as shown in earlier studies of other Arctic and alpine species (Kielland 1994;Raab et al 1996;Schimel and Chapin 1996;Lipson and Monson 1998). Wilson and Jefferies (1996) also showed that in this salt marsh, net N mineralization rates were either very low or negative in early and mid-summer, a finding similar to the studies of Hart and Gunther (1989), Giblin et al (1991), Jonasson et al (1993Jonasson et al ( , 1996 and Schmidt et al (2007). Although these estimates are based on the use of the buried bag technique which may underestimate net N mineralization rates, as senescing roots and root hairs, which provide a source of N, are not included (Jonasson et al 2004).…”
Section: Discussionsupporting
confidence: 67%
“…At grubbed sites the N content of the surface layer of soil is low compared with soils beneath intact swards (McLaren and Jefferies 2004;Buckeridge and Jefferies 2007). In this marsh, rates of net mineralization of soil N in vegetated plots during the first two-thirds of summer are either very low or are negative (Wilson and Jefferies 1996), similar to results from other studies (Hart and Gunther 1989;Giblin et al 1991;Jonasson et al 1993Jonasson et al , 2006Schmidt et al 1999). Mineralization rates rise in the late summer months (Wilson and Jefferies 1996) but in contrast to the studies described above, graminoid swards have been intensely grazed by herbivores (lesser snow geese, Chen caerulescens caerulescens) during the post-hatch period in summer for at least 40 years (Cooke et al 1995).…”
Section: Introductionsupporting
confidence: 78%
“…The fluctuations suggest large and rapid cycles of mobilization and immobilization of microbial nutrients, which are overlooked if sampling is done with larger time intervals. Indeed, it is possible that earlier reported high net nutrient mineralization rates in arctic soils during winter, measured as differences between autumn and spring content of soil inorganic N and P (Giblin et al, 1991;Nadelhoffer et al, 1992;Jonasson et al, 1993;Hobbie and Chapin, 1996; may reflect a high rate of mineralization in early spring rather than throughout the winter. Brooks et al (1998) suggested that freeze-thaw cycles were the main cause of decreased microbial biomass during snowmelt, and other studies have shown microbial diebacks when soils are exposed to freeze-thaw cycles (Schimel and Clein, 1996;Larsen et al, 2002), but initiated grazing by the soil fauna may also affect the microbial community (Ruess et al, 1999).…”
Section: Microbial Biomass Dynamicsmentioning
confidence: 99%
“…While water has both a flushing effect and an impact on soil moisture, which in turn controls oxygen status and microbial degradation, the flow paths and spatial distribution of water in the catchment can also be important in determining material export [Kling, 1995;Kashulina et al, 1998;Frank et al, 2000]. This effect of spatial heterogeneity extends to vegetation patterns and to the influence of different plant types on soil water nutrient concentrations and fluxes Giblin et al, 1991;Scott et al, 2001;Judd and Kling, 2002], although the underlying controls may be related more to plant production and exudates than to decomposition. Clearly, however, the processes of organic matter production and decomposition, interacting with hydrological flows, are fundamental to our understanding of material production and export in all environments.…”
Section: Introductionmentioning
confidence: 99%